Investigation of price, warranty length and production quantity on profit under free replacement warranty policy. Issue 4 (1st October 2016) - Jeyakumar, K.; Krishnaveni, A.; Paul Robert, T.; Jebakani, D.
Abstract: Product pricing, production quantity and warranty length play an important role in maximizing the expected profit of any manufacturing Industry. The profit maximization models reported in the literature have considered only product price and warranty length as decision variables. It is found from the literature that the development of profit maximization models with the decision variables, namely price of the product, warranty length and also the quantity of production is scarcely reported in the literature. Hence, in this study, a profit maximization model for Free Replacement Warranty policy (FRW) under static sales market for a single period with price, warranty length and production quantity as decision variables has been proposed. A numerical illustration is provided to show the theoretical prediction and applicability of the model.